Effectiveness Of Ethanol Extract Of Turmeric (Curcuma Domestic Valet) Gel Against Grade Iia Burn In White Rats (Rattus Norvegicus) - Risyad Rizki Maulidi; Ermi Girsang; Ali Napiah Nasution; Sahna Ferdinand Ginting (International Journal of Health and Pharmaceutical (IJHP), 2022)
This study aims to determine the acceleration of burn wound healing in rats given ethanol extract of turmeric rhizome (Curcuma Domestica Valet) gel and to see the granulation of the skin histopathology of rats. This research method is experimental with a post-test-only design. The research location is in the UNPRI Bio-Molecular Laboratory with 24 rat samples. Treated with Turmeric Rhizome Extract Gel with Concentrations of 25%, 50%, 75%, and 100% and Silver Sulvadizine as Positive Control and Gel as Negative Control. The results showed that the effectiveness of the best Turmeric Rhizome Extract Gel for wound healing was a concentration of 100% on the 21st day of 15 mm. the worst diameter was the negative control on the 21st day of 20 mm. This happens in the healing of burns because of the content of tannins and flavonoids. Measurement of the granulation tissue diameter on the histopathological picture with the results of a concentration of 100% with a thickness of 863 m. Hypothesis test Ha is accepted There is Effectiveness of Ethanol Extract of Turmeric Rhizome Extract (Curcuma Domestica VALET) in Healing Grade IIA Burns. Suggestion It is necessary to do further research related to the factors that cause weak anti-inflammatory and antibiotic Kunit rhizome Extract Gel against second-degree burns.